PENERAPAN METODE WATERFALL PADA SISTEM INFORMASI MANAJEMEN BUKU PERPUSTAKAAN BERBASIS WEB - Achyani, Yuni Eka; Saumi, Sela (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2019)
The development of increasingly advanced information technology can provide many benefits for completing work quickly and accurately. One example that requires the delivery of information quickly and accurately is the field of library, this is in accordance with the function of the library which is the heart of education. Most libraries are still many who adhere to a conventional system, of course this will result in disruption of the continuity of the process of managing books in the library. Therefore, the author takes the theme of this study regarding Library Book Management Information Systems Based on Websites by using the waterfall method on software development as well as methods of observation and literature on data collection. This Information System is the best solution for problem solving in managing library books. With the use of managed computer data technology becomes faster, reducing inefficient time and reducing the occurrence of errors in processing data.